2006
DOI: 10.3852/mycologia.98.6.949
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics of the gomphoid-phalloid fungi with an establishment of the new subclass Phallomycetidae and two new orders

Abstract: Molecular phylogenetic analyses for the gomphoid-phalloid fungi were conducted based on the five gene dataset with extensive taxon sampling. The monophyly of the gomphoid-phalloid clade was strongly supported, and four well supported major subclades were recognized. Three of the four subclades were represented entirely by gastroid taxa, and only Gomphales contained both gastroid and nongastroid taxa. While the gastroid morphology is derived from epigeous, nongastroid taxa in Gomphales, the topology of Phallale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 38 publications
7
62
1
2
Order By: Relevance
“…Peintner et al 2001;Lebel and Syme 2012). In contrast, there are also examples of sequestrate genera that are monophyletic in lineages such as the Hysterangiales and the Boletaceae (Hosaka et al 2006;. Some families have both independent sequestrate genera and genera that contain mixtures of non-sequestrate and sequestrate taxa, such as in the Agaricaceae, where the sequestrate Endoptychum has been subsumed within Chlorophyllum, Agaricus and Macrolepiota, but the monotypic Barcheria is an independent sequestrate genus (Lebel and Syme 2012).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Peintner et al 2001;Lebel and Syme 2012). In contrast, there are also examples of sequestrate genera that are monophyletic in lineages such as the Hysterangiales and the Boletaceae (Hosaka et al 2006;. Some families have both independent sequestrate genera and genera that contain mixtures of non-sequestrate and sequestrate taxa, such as in the Agaricaceae, where the sequestrate Endoptychum has been subsumed within Chlorophyllum, Agaricus and Macrolepiota, but the monotypic Barcheria is an independent sequestrate genus (Lebel and Syme 2012).…”
Section: Introductionmentioning
confidence: 95%
“…Starting trees (shared across runs) were reconstructed for each lineage using RAxML (Stamatakis 2006). The substitution model used was the general time-reversible model with parameters that estimated the proportion of invariable sites and that accommodated rate heterogeneity (GTR+I+G), which followed previous studies (Hosaka et al 2006;Matheny et al 2009;Baroni and Matheny 2011;Skrede et al 2011; Matheny , 2012Lebel and Syme 2012). Where alignments from multiple loci were available, each locus was unlinked for the substitution model and clock rate and then linked for the tree topology and node ages.…”
Section: Dating Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Ponce de León 1968, Sunhede 1989, Domínguez de Toledo 1996, Kasuya et al 2009). Currently, it is accepted that geastroid species are related to gomphoid/phalloid fungi (Hosaka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The order used to include two families Clathraceae and Phallaceae, with the shared and diagnostic feature of the peridium breaking down at maturity. Based on a phylogenetic analysis using molecular data, a study by Hosaka et al (2006) suggested that the order Phallales should include six families (Clathraceae, Claustulaceae, Lysuriaceae, Phallaceae, Protophallaceae, and Trappeaceae) including some species with peridium not breaking down at maturity. Economically, the order Phallales includes many edible and medicinal species, such as the “veiled lady mushroom,” Phallus indusiatus (syn.…”
Section: Macrofungi That Require Animals For Dispersalmentioning
confidence: 99%